Acceptability study of a co-designed educational game about dementia for children: The Kids Dementia Game - Patrick Stark; Sonya Clarke; Gary Mitchell; Gillian Carter; Stephanie Craig; Christine Brown Wilson (PLoS ONE, 2025)
Background Dementia has physical, psychological, social and economic impacts, not only for people living with dementia, but also for their carers, families and wider society. Due to the growing number of people living with dementia, children are increasingly likely to encounter family members living with dementia. The aim of this project was to pilot an educational game which was co-designed with children and people living with dementia with the intention of improving children’s understanding and perception of dementia. Research design and methods An acceptability study of the Kids Dementia Game was conducted in three classes in three schools in Northern Ireland. This study investigated acceptability of the game and the feasibility of online data collection using a pre-post test methodology to explore how best to collect evaluation data if the game was to be delivered on a larger scale. Results Evaluation of the game with children showed a positive level of acceptability of the game. Children found the game engaging, easy to navigate and fun to play. Feasibility of the data collection method was found to be a barrier to the pre-post test evaluation of the game. Discussion and implications These findings suggest that the game shows evidence of promise for improving public perception and understanding of dementia using an early intervention approach with children.